2006
DOI: 10.1074/jbc.m506864200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Histones by Tissue Transglutaminase

Abstract: Tissue transglutaminase 2 (TG2) has recently been shown to have intrinsic serine/threonine kinase activity. Since histones are known to be cross-linked by TG2, we investigated whether histones are also substrates for TG2 kinase activity. TG2 was able to phosphorylate H1, H2A, H2B, H3, and H4 histones in vitro. Using peptide substrates and phosphospecific antibodies we demonstrated that TG2 phosphorylated Ser 10 in H3 and that this phosphorylation was reduced by acetylation, whereas phosphorylation of Ser 10 by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 37 publications
1
65
0
1
Order By: Relevance
“…5, 10 mM magnesium chloride, [g-32 P]ATP (25 mCi/ml)) for 30 min at 30 8C as described previously (Mishra & Murphy 2004, Mishra et al 2006. The reaction was stopped by the addition of SDS-PAGE sample buffer and the samples were boiled for 5 min.…”
Section: In Vitro Kinase Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…5, 10 mM magnesium chloride, [g-32 P]ATP (25 mCi/ml)) for 30 min at 30 8C as described previously (Mishra & Murphy 2004, Mishra et al 2006. The reaction was stopped by the addition of SDS-PAGE sample buffer and the samples were boiled for 5 min.…”
Section: In Vitro Kinase Assaymentioning
confidence: 99%
“…In addition, we have reported that TG2 has intrinsic kinase activity and phosphorylates a number of proteins including insulin-like growth factor binding protein-3 (IGFBP3; Mishra & Murphy 2004, Mishra et al 2006, 2007a. We have recently found that IGFBP3 has a role in insulin secretion (Nguyen et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The roles of TG2-mediated polyamination or deamidation of glutamine residues and acylation of lysine residues are not fully known. Furthermore, TG2 also acts as a protein disulfide isomerase (194) and as a protein kinase (195)(196)(197) for certain Effects of transglutaminases on vascular and cardiac diseases. The inset depicts a coronary artery with an atheroma that has undergone plaque rupture, with subsequent thrombus formation in the arterial lumen and within the lipid core.…”
Section: Perspectivementioning
confidence: 99%
“…But the Tgase enzyme disclosed itself further as a rich fertile mine, although a careful skepticism is always required in dealing with new astonishing "discoveries". This particularly applies to the reports that Tgase2 can display two additional activities, the former as protein kinase (Mishra et al 2006), the latter as protein disulfide isomerase (Hasegawa et al 2003). At the eyes of one of us (CMB), these activities still require much research to be definitively proved, although it is interesting to note that these activities do not require calcium and for this reason can potentially play important regulatory functions in physiological cellular conditions.…”
Section: Introductionmentioning
confidence: 99%